ENDOCRINE GLANDS AND THEIR FUNCTION (Лучшие интеллектуальные исследования, 2025)
The human body relies on a complex network of systems to maintain internal balance and coordinate various physiological processes, among which the endocrine system plays a crucial role. This system comprises multiple glands that secrete hormones directly into the bloodstream to regulate metabolism, growth, reproduction, and stress responses. These glands include the pituitary, thyroid, adrenal glands, pancreas, and reproductive organs, each performing specific functions essential to homeostasis. Recent research highlights not only the traditional roles of these hormones but also emerging insights into how substances such as endocrine-disrupting chemicals can adversely affect glandular function, particularly in the adrenal glands, by disrupting steroid hormone pathways (Li Z et al.). Additionally, new findings reveal that certain D-amino acids present in endocrine tissues contribute to hormonal regulation, expanding our understanding of the biochemical complexity within these glands (M Katane et al., p. 562-579). To visualize the organization and location of these vital components, a detailed anatomical overview of the human endocrine system is instrumental for contextualizing their interconnected roles .